Dilemmas in donor design: organisational reform and the future of foreign aid agencies - Gulrajani, Nilima (2015)
With growing uncertainty over the value and impact of traditional bilateral foreign aid to advance development in poor countries, there is disquiet about the future of national public agencies and ministries with responsibility for managing and delivering international assistance. Growing reputational damage to foreign aid has triggered a lively discussion in development policy circles about the best structural configuration for organizing and governing international development functions within donor countries. To date, public administration scholars with expertise in questions of bureaucratic design and performance have yet to weigh in on this debate. This article is an attempt to present current controversies about donor governance and offer guidance for resolving current dilemmas by exploring the potential contributions of public administration. - Reproduced.
Keywords: Foreign aid